2011
DOI: 10.2165/11585490-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Pharmacotherapy of Paraphilias

Abstract: Concerns about paraphilia and its treatment have grown in the past few years. Although the aetiology of paraphilia disorder is still not completely understood, pharmacological treatments have been proposed for this disorder. Paraphilias are a major burden for patients and society; nevertheless, only a few individuals with paraphilias voluntarily seek treatment. Antidepressants have been used in the treatment of certain types of mild (e.g. exhibitionism) and juvenile paraphilias. Antilibidinal hormonal treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 90 publications
0
57
0
8
Order By: Relevance
“…Inappropriate treatment may put both the offender (e.g., in case of specific medical conditions) and society at risk (e.g., in case of severe co-morbid psychopathy). Paraphilias are chronic disorders and a minimal duration of 3-5 years of treatment is recommended for severe paraphilia with a high risk of violence (del Busto & Harlow, 2011;Garcia & Thibaut, 2011;Hall & Hall, 2007;Thibaut et al, 2010).…”
Section: Sex Offenders With Acquired Paedophilia: Ethical Questions Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate treatment may put both the offender (e.g., in case of specific medical conditions) and society at risk (e.g., in case of severe co-morbid psychopathy). Paraphilias are chronic disorders and a minimal duration of 3-5 years of treatment is recommended for severe paraphilia with a high risk of violence (del Busto & Harlow, 2011;Garcia & Thibaut, 2011;Hall & Hall, 2007;Thibaut et al, 2010).…”
Section: Sex Offenders With Acquired Paedophilia: Ethical Questions Rmentioning
confidence: 99%
“…Moreover, Garcia and Thibaut (2011) report that between 33-52% of paraphiliac individuals suffer from personality disorders such as borderline or antisocial personality disorders. Raymond, Coleman, Ohlerking, Christenson, and Miner (1999) found that 22.5% of sex offenders with paedophilia suffer from antisocial personality disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 19th century, Freud suggested that the cause of sexual perversion involves biological and developmental factors, as well as psychoanalytic factors (1). In recent years, researchers defined paraphilia as the addictive, impulsive, and compulsive expression of excessive sexual desire (2).…”
Section: Introductionmentioning
confidence: 99%
“…Pacientes informados e motivados são aqueles que melhor respondem ao tratamento (Assumpção et al, 2014). (Rösler;Witztum, 1998;Kafka, 2007;Thibaut, 2011;Assumpção et al, 2014). …”
Section: Inibidores Seletivos Da Recaptação De Serotoninaunclassified
“…O tratamento dos casos de parafilias moderadas a graves respondem melhor ao uso de terapias de deprivação androgênica, associadas à psicoterapia de base cognitivocomportamental (Rösler;Witztum, 1998;Briken et al 2003;Kafka, 2007;Thibaut, 2011). Neste caso, o uso de medicações antiandrogênicas -proscrito no Brasil para os casos de parafilias -impediria a realização de estudos com desenhos que incluíssem estas medicações.…”
Section: Implicações Para Futuras Pesquisasunclassified